IMPLICATIONS of ARTICLE 16 SECTION (3) OF 28 YEAR 2014 ON COPYRIGHT AS A FIDUSIA GUARANTEE OBJECT - Budi Hermono (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Article 16 section (3) of the Copyright Law which stated that copyright can be used as an object of fiduciary is revolutionary in Indonesian law. Copyright is an intangible movable object which has level of difficulty to assess its value. The value of objects is an important thing when it used as objects of fiduciary. The value is equivalent to that of the creditor (fiduciary recipient) will provide a sense of security for the creditor for returning their loan. The application of Article 16 section (3) of the Copyright Law has not been accompanied by an implementing regulation for financing institutions as fiduciary recipients, especially in the standard of assessment of the value of copyright proposed as an object of fiduciary. Financial Services Authority (OJK) needs to formulate regulations that provide copyright standardization used as objects of fiduciary to provide legal certainty for the creditor. Keywords: copyrights, fiduciary, object of fiduciary